Adult and Continuing Education in Belarus - Veramejchyk, Galina (Länderportäts, 2017)
This publication gives an overview of central aspects of adult and continuing education in Belarus. Galina Veramejchyk presents a range of data and information regarding adult and continuing education institutions, ¿nancing, provision, participation, staff and international relationships. She describes adult and continuing education in Belarus taking into consideration the political, geographical, and cultural context as well as the current economic situation.This book offers a brief and systematic introduction and guides the reader through the system of adult and continuing education in Belarus.